Kepuasan Pelanggan berdasarkan Dimensi Timeliness Kualitas Jasa Evans dan Lindsay dengan Metode Importance Performance Analysis - Puput Hermanti (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2017)
Based on Keputusan Menteri Pendayagunaan Aparatur Negara Nomor KEP/25/M.PAN/2004  level of customer satisfaction of a service can be judged by the Community Satisfaction Index, there are fourteen elements of these services have a standard that is equal to 85%. General clinic and specialist in Menur Mental Hospital Surabaya  has a Community Satisfaction Index by 75.11% which is below the standard of 85%. This research was purposed to analyzing customer satisfaction  based on the level of importance of hospital performance in timeliness dimension of Evans and Lindsay service quality with importance performance analysis method. The research design  was observational with cross sectional approach. Research conducted on November  2016 included 98 customer in General clinic and Specialist in Menur Mental Hospital Surabaya  as respondents. Data were analyzed by Importance Performance Analysis. The result showed respondents considered that all aspects of the timeliness dimension is very important, especially for check the wait time ≤ 60 minutes aspect with mean importance  value is 3.58, and performance service respondents considered check wait time ≤ 60 minutes aspect had smaller mean value performance (2.44) from the mean performance timeliness (2.84). The conclusion is customer not satisfied with timeliness dimension of Evans and Lindsay service quality. Keywords: Customer Satisfaction,  Importance-Performance Analysis, Timeliness